Preservation and Packaging Methods to Extend the Shelf Life of Fresh Lontar (Borassus flabellifer L.) Pulp - Dewi Pratiwi Sasmito; Emmy Darmawati; Rokhani Rokhani (The University of Lampung, 2025)
Lontar is a palm with fruits having a various important biomolecules containing proteins, carbohydrates, vitamins, and minerals, which are beneficial to human health. The shelf life of lontar fruit pulp is generally limited to approximately 1–2 days. The objective of this study was to analyze the effect of water amount and citric acid concentration combining with packaging types and temperature ranges on the quality of fresh lontar fruit pulp and the shelf life of the pulp. The research used Response Surface Methodology with a Central Composite Design as the design model to find the best combination of water and citric acid concentration. The selected combination was applied in preservation treatment with polypropylene and nylon packaging under storage temperatures of 15 °C and 25–28 °C. The quality parameters observed included brightness, hardness, pH, and total dissolved solids, as well as organoleptic tests. The optimization results indicated that the optimal ratio of water to citric acid concentration was 40 ml to 0.2%. Cold storage significantly extended the shelf life of lontar fruit pulp to 6 days, compared to just 3 days at room temperature. The organoleptic test results showed that PP packaging received a higher level of favorability compared to nylon packaging.